(untitled) (International Journal of Physiotherapy, 2015)
Background: Low back pain is one of the common complaints seen in cricketers. Core stability is defined as the ability to control the position and motion of the trunk over the pelvis to allow optimum production, transfer and control of force and motion to the terminal segment in integrated athletic activities and generally given as treatment in many instances. No randomized controlled studies were there for low back pain in cricketers. So, purpose of this study was to know the efficacy of Swiss ball(SB), Thera-band(TB), and Floor exercises(FE) in cricketers with low back pain. Methods: Sixty male competitive cricket players between 15-35 years age were randomly assigned into 4 groups. SB (n=15), TB (n=15), FE (n=15), control group (n=15). Analysis of data within group and between groups of the pre and post treatment values of pain-disability(Modified Oswestry Low Back Pain Questionnaire) and core strength(double-leg lowering test) was done statistically using t test and ANOVA test. Results: The results of within group analysis, showed extremely significant improvement in terms of pain & disability and back strength (p<0.0001) in all the groups, whereas in between groups, TB(theraband) group showed significant improvement compared to SB(swissball), FE(floor-exercise) and control groups. Conclusion: The results revealed that Thera-band (TB) group had better improvement than the other three groups in decreasing low back pain and improving core stability.